Dampak Pengembangan Kawasan Ekonomi Khusus (KEK) Mandalika Terhadap Penurunan Daya Saing Destinasi Wisata Senggigi: Pendekatan Kuantitatif Berbasis Persepsi Stakeholder - Sulastri Rahayu Dewi; Muhammad Firmansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of the Mandalika Special Economic Zone (KEK) has given rise to the phenomenon of decreasing the competitiveness of the Senggigi tourist destination as a tourist area that developed earlier. This research aims to analyze the impact of the development of the Mandalika SEZ on reducing the competitiveness of the Senggigi tourist destination by considering the perceptions of tourism stakeholders. The research approach used was quantitative by distributing questionnaires to 115 respondents consisting of Business Actors, Government/Private, Academics, Community, and Media/Influencers. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results show that promotion and competition variables have a significant effect on destination competitiveness, while facilities and accessibility do not have a significant effect. The coefficient of determination (R²) value of 0.641 indicates that the exogenous construct has strong explanatory power regarding endogenous variables. These findings confirm that adaptive promotional strategies and increasing competitiveness based on collaboration are the keys to the revitalization of Senggigi amidst the dominance of the Mandalika SEZ development.